2017
DOI: 10.1063/1.4998459
|View full text |Cite
|
Sign up to set email alerts
|

Controlling resonance energy transfer in nanostructure emitters by positioning near a mirror

Abstract: The ability to control light-matter interactions in quantum objects opens up many avenues for new applications. We look at this issue within a fully quantized framework using a fundamental theory to describe mirror-assisted resonance energy transfer (RET) in nanostructures. The process of RET communicates electronic excitation between suitably disposed donor and acceptor particles in close proximity, activated by the initial excitation of the donor. Here, we demonstrate that the energy transfer rate can be sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 58 publications
(67 reference statements)
0
23
0
Order By: Relevance
“…A presence of boundaries is one of such circumstances. It has been shown that the presence of a conducting plate induces modifications in the interatomic potential of two atoms in their ground states [13,14,62], the near-surface effect sufficiently changes the resonance interaction between an excited atom and a ground-state atom [63], and suitably arranged structured environments can significantly affect the resonance energy transfer process [64][65][66]. These works refer to two uncorrelated atoms or molecules.…”
Section: Introductionmentioning
confidence: 99%
“…A presence of boundaries is one of such circumstances. It has been shown that the presence of a conducting plate induces modifications in the interatomic potential of two atoms in their ground states [13,14,62], the near-surface effect sufficiently changes the resonance interaction between an excited atom and a ground-state atom [63], and suitably arranged structured environments can significantly affect the resonance energy transfer process [64][65][66]. These works refer to two uncorrelated atoms or molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Resonant optical microcavities [20,[34][35][36], nanoparticle arrays [37][38][39], single nanoparticles [40][41][42][43], subwavelength apertures [44,45] and nanoantennas [46][47][48] have been reported to enhance the energy transfer rate, while other studies on mirrors [49][50][51][52], microcavities [53,54], nanoparticles [55][56][57] and plasmonic antennas [58,59] reported no effect on the FRET rate.…”
Section: Introductionmentioning
confidence: 99%
“…Inter alia, the QED analysis also showed that the two supposedly different mechanisms can never compete in determining the distance-dependent dynamics of energy transfer. The results, which have now become standard textbook material in the field of nano-optics [45], have found recent applications on energy transfer in engineered nanoscale structures [149,150].…”
Section: A Differences In Perspectivementioning
confidence: 99%